Institutional Quality and Academic Ahievement - Neira Pontón, María Daniela (2024)
The absence of education quality in nations explains a considerable share of the disparities in growth and development between emerging and developed economies. Institutional quality refers to the regulations and incentives that shape the behavior of our societies, including the educational environment, and is one of the factors that can improve the quality of education. The main objective of this study is to understand how the levels of institutional quality in a country are associated with increases in the average academic performance of a country, at the school level. The sample used covers the average PISA scores of 47 countries, in a tri-annual panel data set of 5 periods. This paper uses Cochrane-Orcutt method with the necessary adjustments for an unbalanced panel data set. The main results provide evidence that better levels of institutional quality have a positive association with academic achievement. One of the main transmission channels is public spending on education, considering that institutional quality can function as a proxy for the efficiency of decisions made in resource assignment in education.